2023
DOI: 10.3390/su151612353
|View full text |Cite
|
Sign up to set email alerts
|

Research on Carbon Emission Structure and Model in Low-Carbon Rural Areas: Bibliometric Analysis

Abstract: As the energy crisis and environmental problems are exacerbated, rural carbon emissions have gradually attracted increasing attention. Meanwhile, rural areas have the important function of ecological carbon sequestration, so the research field of carbon emissions has gradually expanded from urban to rural areas in recent years. To systematically sort out the research progress regarding low-carbon rural areas, a total of 583 papers published during 2013–2023 were acquired through the bibliometric analysis metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 72 publications
0
0
0
Order By: Relevance
“…where E e is the carbon emissions of electric power, E f represents the electric power consumption obtained from China Rural Energy Yearbook (2022) [46], which were released by the local power companies. γ is the electricity emission factor, derived from the Baseline Emission Factors for Regional Power Grids in China [17], with a value of 0.928 kg (CO 2 )/kWh.…”
Section: Carbon Emissionsmentioning
confidence: 99%
See 1 more Smart Citation
“…where E e is the carbon emissions of electric power, E f represents the electric power consumption obtained from China Rural Energy Yearbook (2022) [46], which were released by the local power companies. γ is the electricity emission factor, derived from the Baseline Emission Factors for Regional Power Grids in China [17], with a value of 0.928 kg (CO 2 )/kWh.…”
Section: Carbon Emissionsmentioning
confidence: 99%
“…Scholars have posited that mixed-use villages have become one of the main sources of China's carbon emissions [16], which could hinder China's efforts towards its "Dual Carbon" goals. At the same time, this has led to various social, economic, and environmental problems [17], such as harm to the rural environment, negative effects on villagers' health, and a widening gap between urban and rural areas, rendering rural development unsustainable.…”
Section: Introductionmentioning
confidence: 99%
“…Relevant studies show that there are differences in energy consumption and industrial layout in villages of different regions, which leads to the different composition of carbon emissions, but according to the currently available papers, it can be found that scholars have carried out some calculations, evaluations and predictions of single-factor carbon sources and sinks in rural production activities, such as building operation [7], agricultural production [8], animal husbandry [9], photovoltaic carbon sinks, and so on [10]. The results have proved that rural buildings are important carriers of carbon emissions in production and life, and the energy use and production activities generated therein are one of the main sources of global greenhouse gases [11,12]. Due to its characteristics, rural development often lags behind urban development [13], and the same is true for energy use.…”
Section: Introductionmentioning
confidence: 99%